PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA UNIT KERJA PENGADAAN BARANG/JASA PEMERINTAH DI KDPDT - Novia Causal Wismaya; Francy Iriani (Ikatan Dosen Menulis, 2025)
This study aims to analyze the influence of leadership and communication styles on employee performance in the Goods/Services Procurement Work Unit (UKPBJ) of the Ministry of Villages and Development of Disadvantaged Regions, with work motivation as a mediating variable. The research background stems from the decline in the Procurement Governance Index (ITKP) score which indicates organizational performance challenges, thus requiring research on leadership, communication, and work motivation within the UKPBJ environment. A quantitative approach was used on the entire population (saturated sample) of 75 employees involved in the procurement process; data were collected through questionnaires and analyzed using SEM-PLS through testing the measurement model (convergent validity/AVE, discriminant, reliability) and structural model. The results show: leadership style has a positive and significant effect on work motivation and performance, communication has a significant effect on work motivation but does not directly affect performance, work motivation partially mediates the effect of leadership style on performance, and fully mediates the effect of communication on performance. These results confirm that improving UKPBJ performance is more effectively achieved through strengthening motivational leadership practices as well as communication interventions that are explicitly directed at raising employee motivation before they impact performance. Practical implications include strengthening the role of leaders as role models, structuring communication channels and feedback, and designing motivational policies to accelerate performance improvement